2022
DOI: 10.3390/mti6090075
|View full text |Cite
|
Sign up to set email alerts
|

Current Challenges and Future Research Directions in Augmented Reality for Education

Abstract: The progression and adoption of innovative learning methodologies signify that a respective part of society is open to new technologies and ideas and thus is advancing. The latest innovation in teaching is the use of Augmented Reality (AR). Applications using this technology have been deployed successfully in STEM (Science, Technology, Engineering, and Mathematics) education for delivering the practical and creative parts of teaching. Since AR technology already has a large volume of published studies about ed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(15 citation statements)
references
References 113 publications
0
15
0
Order By: Relevance
“…Ref. [31] includes a review of the present literature, an investigation of the problems, the identification of prospective study areas, and lastly, reports on the construction of two case studies that can highlight the initial steps needed to address these research areas. The findings of this study, finally, reveal the research gap needed to enable real-time touchless hand interaction, kinesthetic learning, and ML agents using a remote learning methodology.…”
Section: Related Workmentioning
confidence: 99%
“…Ref. [31] includes a review of the present literature, an investigation of the problems, the identification of prospective study areas, and lastly, reports on the construction of two case studies that can highlight the initial steps needed to address these research areas. The findings of this study, finally, reveal the research gap needed to enable real-time touchless hand interaction, kinesthetic learning, and ML agents using a remote learning methodology.…”
Section: Related Workmentioning
confidence: 99%
“…Virtual agents and bots have emerged to assist end-users in performing tasks supported by AR and also improve social interactions and motivation [11]. In children's education, virtual agents have proven to help a participant in a learning task and promote collaborative learning by enhancing emotional abilities [12]. As Iqbal et al [12] demonstrated in their latest systematic review, AR agents are new and have not been effectively implemented in any AR studies for education, as discussed in detail.…”
Section: Of 13mentioning
confidence: 99%
“…For this reason, various studies have rightly documented the potential of using AR in various ‘hands‐on’ educational and learning practices (Akdeniz, 2016; Yeh & Tseng, 2020). On the other side, it will also have a great impact on the industrial growth and economy of a developing country (Iqbal et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, various studies have rightly documented the potential of using AR in various 'hands-on' educational and learning practices (Akdeniz, 2016;Yeh & Tseng, 2020). On the other side, it will also have a great impact on the industrial growth and economy of a developing country (Iqbal et al, 2022). Thus, based upon the studies and the findings of different researchers, the biggest potential of AR is mainly due to visually attractive and engaging graphics with rich multimedia features that provide multiple possibilities for interaction and engagement in response to feedback received by users as a result of their actions in real-time (Saltan & Arslan, 2016).…”
mentioning
confidence: 99%